The United States' record-low child poverty rate in international and historical perspective - Zachary Parolin; Stefano Filauro (Luxembourg Income Study (LIS), 2023)
In 2021, the federal government of the United States (US) expanded a set of income transfers that led to strong reductions in child poverty. This research note uses micro-data from more than 50 countries, and US data spanning more than 50 years, to place the 2021 child poverty rate in historical and international perspective. We demonstrate that whether using the Supplemental Poverty Measure (SPM), relative poverty measures, or an absolute poverty measure, the US child poverty rate in 2021 was at its lowest level since at least 1967. The US tax and transfer system reduced the 2021 SPM child poverty rate by more than 75 percent relative to the pre-tax/transfer child poverty rate, three times greater than its mean reduction effect between 1967-2019. Internationally, the policy changes improved the US's standing from having a relative poverty rate twice that of Germany's in 2019 to the same as Germany's in 2021. Moreover, the US tax and transfer system progressed from reducing child poverty at less than half the rate of Norway in 2019 to a rate comparable with Norway in 2021. However, the US's success was temporary: after the expiration of the 2021 income provisions, the child poverty rate doubled and returned to being higher than in most other high-income countries.
Keywords: 330; child poverty; Child Tax Credit; child well-being; poverty